HipHop zwischen Istanbul und Berlin: Eine (deutsch-)türkische Jugendkultur im lokalen und transnationalen Beziehungsgeflecht - Kaya, Verda (transcript, 2015)
Between identification and distancing: a well-informed study about Hip Hop culture in Berlin and Istanbul among German-Turkish and Turkish Youths.